1985
DOI: 10.1128/iai.48.2.480-485.1985
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Lactobacillus casei on Pseudomonas aeruginosa infection in mice

Abstract: The protective effect of heat-killed Lactobacillus casei YIT9018 (LC 9018) against Pseudomonas aeruginosa infection in mice was compared with that of Corynebacterium parvum. Survival of mice after intraperitoneal (i.p.) infection with P. aeruginosa was augmented in mice that had been pretreated i.p. with LC 9018 5 days previously. Similar treatment of mice with C. parvum, however, was not effective at all. Moreover, mice became more susceptible to infection with P. aeruginosa after such treatment. Growth of P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…Lactobacillus casei strain Shirota (LcS) was originally isolated from the faeces of healthy humans and is widely used as a starter for fermented milk products. It has been well established that LcS can activate cellular immunity of the host, and LcS has been studied intensively with regard to its anti‐tumour and anti‐infectious activities [4–6]. Our recent paper [7] showed a novel ability of LcS to suppress IgE secretion from antigen‐stimulated splenocytes, and suggested a possible use of LcS in preventing IgE‐mediated allergy.…”
Section: Introductionmentioning
confidence: 99%
“…Lactobacillus casei strain Shirota (LcS) was originally isolated from the faeces of healthy humans and is widely used as a starter for fermented milk products. It has been well established that LcS can activate cellular immunity of the host, and LcS has been studied intensively with regard to its anti‐tumour and anti‐infectious activities [4–6]. Our recent paper [7] showed a novel ability of LcS to suppress IgE secretion from antigen‐stimulated splenocytes, and suggested a possible use of LcS in preventing IgE‐mediated allergy.…”
Section: Introductionmentioning
confidence: 99%
“…We ascertained preliminarily that the facultative anaerobes detected in the feces of the mice were mainly E. coli. E. coli was thought to be the main translocating bacteria in mice after X-ray irradiation (7), and Lactobacilli were reported to be the potent immune stimulants (11,15). In our previous study, the administration of immune milk resulted in a decrease in the number of E. coli in the feces at all points before and after irradiation and an increase in the number of Lactobacilli after irradiation (8).…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment of mice with L. casei increased the survival of mice inoculated with Pseudomonas aeruginosa intraperitoneally [95] and into thermal injury wounds [96]. The authors suggested that the protective effect of the lactobacilli was afforded by activated macrophages, interferon production and accumulation of phagocytes which cleared the infecting bacteria [94,95,[97][98][99]. Studies initiated by Bogdanov et al [100] into the antitumour substance of Lactobacillus bulgaricus, blastolysin, have shown that the active component of the antitumour drug is a tetrasaccharide-containing muramylpeptide [101] which stimulates production of cytokines such as tumour necrosis factor and interferon [102,103].…”
Section: Stimulation Of the Immune Systemmentioning
confidence: 98%
“…Subcutaneous [93] and intraperitoneal [94] injection of L. casei and L. acidophilus respectively stimulated the listericidal activity of mouse peritoneal 258 macrophages. Pretreatment of mice with L. casei increased the survival of mice inoculated with Pseudomonas aeruginosa intraperitoneally [95] and into thermal injury wounds [96]. The authors suggested that the protective effect of the lactobacilli was afforded by activated macrophages, interferon production and accumulation of phagocytes which cleared the infecting bacteria [94,95,[97][98][99].…”
Section: Stimulation Of the Immune Systemmentioning
confidence: 99%